Education, Culture, Technology and Innovation as Drivers of Social Change. - Alfonzo Villegas, Nohelia Yaneth (Conexiones UG, 2025)
The article analyses the interrelation between education, culture, technology and innovation as fundamental drivers of social change. It is the product of a documentary review of articles, books, reports and indexes from the year 2024 related to the subject. The result is a heterogeneous panorama and scattered data, with some persistent advances and challenges: increased access to higher education more in undergraduate than in postgraduate education, prevalence of private education over public education, which is why access gaps persist for some socioeconomic groups, advances in female participation, even though inequalities remain in areas such as STEAM careers and leadership positions. Greater investment is required in infrastructure and resources, especially related to the incorporation of technology and AI, which affects quality. Collaboration between Latin American universities and those from other regions must be emphasized to strengthen research and the training of human talent. Investment in R&D remains insufficient, which hinders innovation, which is why greater participation of the productive sector is required. It is concluded that higher education in the Latin American region must strengthen the development of soft skills such as critical thinking, creativity and active citizenship, supported by culture, to provide a sense of identity and belonging conducive to inclusion and diversity, through greater promotion of artistic and cultural education. Technology and innovation, as catalysts for change, must be incorporated into the university curriculum.
Keywords: Social change; culture; higher education; innovation; technology